Synthesis, Characterization and Evaluation of Some 5-Substituted 1,3,4-Oxadiazole-2-thioesters as Antifungal Agents - Hasan, Aurangzeb; Rezaul Karim Sheikh, Md; Gapil, Shelly (Asian Journal of Chemistry, 2012)
A series of 5-substituted 1,3,4-oxadiazole-2-thioesters was synthesized by converting several substituted organic acids successively into the corresponding esters, hydrazides and 5-substituted 1,3,4-oxadiazole-2-thiols. Finally the target compounds: 5-substituted 1,3,4-oxadiazole-2- thioesters were obtained by refluxing 5-substituted 1,3,4-oxadiazole-2-thiols in the presence of acid chloride and potassium hydroxide. The structures of the synthesized compounds were established by physicochemical and spectroscopic methods. The synthesized compounds were evaluated for their in vitro antifungal activity. Some of the evaluated compounds possessed significant antifungal activity as compared to a terbinafine standard.